EXERCISE 2C
Question 1:
By actual division, find the quotient and the remainder when (x4 + 1) is divided by (x – 1).
Verify that remainder = f(1).
Question 2:
Verify the division algorithm for the polynomials p(x)=2x4−6x3+2x2−x+2 and g(x)=x+2.
Question 3:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 3:
By remainder theorem, when p(x) is divided by (x − 1), then the remainder = p(1).
Putting x = 1 in p(x), we get
∴ Remainder = 7
Thus, the remainder when p(x) is divided by g(x) is 7.
Question 4:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 4:
By remainder theorem, when p(x) is divided by (x − 3), then the remainder = p(3).
Putting x = 3 in p(x), we get
∴ Remainder = 5
Thus, the remainder when p(x) is divided by g(x) is 5.
Question 5:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 5:
By remainder theorem, when p(x) is divided by (x − 2), then the remainder = p(2).
Putting x = 2 in p(x), we get
∴ Remainder = 6
Thus, the remainder when p(x) is divided by g(x) is 6.
Question 6:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 6:
By remainder theorem, when p(x) is divided by (2x − 3), then the remainder = .
Putting in p(x), we get
∴ Remainder = 3
Thus, the remainder when p(x) is divided by g(x) is 3.
Question 7:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 7:
By remainder theorem, when p(x) is divided by (x + 1), then the remainder = p(−1).
Putting x = −1 in p(x), we get
∴ Remainder = 4
Thus, the remainder when p(x) is divided by g(x) is 4.
Question 8:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 8:
By remainder theorem, when p(x) is divided by (x + 2), then the remainder = p(−2).
Putting x = −2 in p(x), we get
∴ Remainder = 6
Thus, the remainder when p(x) is divided by g(x) is 6.
Question 9:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 9:
By remainder theorem, when p(x) is divided by (3x + 2), then the remainder = .
Putting in p(x), we get
∴ Remainder = 7
Thus, the remainder when p(x) is divided by g(x) is 7.
Question 10:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 10:
By remainder theorem, when p(x) is divided by , then the remainder = .
Putting in p(x), we get
∴ Remainder =
Thus, the remainder when p(x) is divided by g(x) is .
Question 11:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 11:
By remainder theorem, when p(x) is divided by , then the remainder = .
Putting in p(x), we get
∴ Remainder = 3
Thus, the remainder when p(x) is divided by g(x) is 3.
Question 12:
Using the remainder theorem, find the remainder, when p(x) is divided by g(x), where
.
Answer 12:
By remainder theorem, when p(x) is divided by (x − a), then the remainder = p(a).
Putting x = a in p(x), we get
∴ Remainder = 5a
Thus, the remainder when p(x) is divided by g(x) is 5a.
Question 13:
The polynomials when divided by (x – 2) leave the same remainder. Find the value of a.
Answer 13:
Let and .
By remainder theorem, when f(x) is divided by (x – 2), then the remainder = f(2).
Putting x = 2 in f(x), we get
By remainder theorem, when g(x) is divided by (x – 2), then the remainder = g(2).
Putting x = 2 in g(x), we get
It is given that,
Thus, the value of a is 8.
Question 14:
Answer 14:
Thus, we have:
And,
Now,
By putting the value of b, we get the value of a, i.e., 5.
∴ a = 5 and b = 8
Now,
Also,
Thus, we have:
Question 15:
If , show that p(x) is not a multiple of g(x).
Answer 15:
Putting x = 2 in p(x), we get
Therefore, by factor theorem, (x − 2) is not a factor of p(x).
Hence, p(x) is not a multiple of g(x).
Question 16:
If , show that g(x) is not a factor of p(x).
Answer 16:
Putting in p(x), we get
Therefore, by factor theorem, (2x + 1) is not a factor of p(x).
Hence, g(x) is not a factor of p(x).
No comments:
Post a Comment